2019
DOI: 10.1002/bio.3671
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic red fluorescence enhancement and emission red shift of carbon dots following Zn/ZnO decoration

Abstract: Metal atom doping, an easy and convenient method, can optimize and tune the physical-chemical properties and photometrics of carbon dots (CDs). However, there are few reports on the preparation of metal-decorated CDs that give red emission and a high photoluminescence quantum yield (PLQY). Here, we demonstrate a zinc (existing in human body) ion-doping strategy to observably enhance the PLQY and lengthen the CD emission wavelength. The prepared Zn/ZnO-decorated CDs (Zn-CDs) produced red fluorescence (623 nm) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The peak of OH – contracted while the peak of lattice O 2 – increased in the recovered samples, consistent with the FTIR results . The high-resolution XPS spectra of Zn 2p exhibited peaks at 1044.9 and 1021.9 eV, assigned to Zn 2p 1/2 and Zn 2p 1/2 , respectively, which did not show significant changes after the reaction . The XPS spectral lines of Co 2p are shown in Figure a.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The peak of OH – contracted while the peak of lattice O 2 – increased in the recovered samples, consistent with the FTIR results . The high-resolution XPS spectra of Zn 2p exhibited peaks at 1044.9 and 1021.9 eV, assigned to Zn 2p 1/2 and Zn 2p 1/2 , respectively, which did not show significant changes after the reaction . The XPS spectral lines of Co 2p are shown in Figure a.…”
Section: Resultssupporting
confidence: 84%
“…32 The high-resolution XPS spectra of Zn 2p exhibited peaks at 1044.9 and 1021.9 eV, assigned to Zn 2p 1/2 and Zn 2p 1/2 , respectively, which did not show significant changes after the reaction. 33 The XPS spectral lines of Co 2p are shown in Figure 4a. Two major peaks located at 797.1 and 781.0 eV were attributed to Co 2p 1/2 and Co 2p 3/2 , respectively, and two shake-up satellite peaks of the cobalt ions were observed at 803.1 and 786.1 eV.…”
Section: Stability and Practicabilitymentioning
confidence: 99%
“…The wide scan survey spectrum illustrates the characteristic peaks correspond to C1s (286.49 eV), N1s (400.45 eV) and O1s (534.32 eV), confirmed that GB‐CDs were mainly composed of C, N, and O (figure A). The high‐resolution C 1s spectrum revealed four peaks located at 285.69, 286.77, 288.64 and 287.64 eV, which ascribed C=C/C−C, C−N, C=O and C−O moieties respectively (Figure B) . Furthermore, the XPS spectrum of N 1s revealed four peaks at 399.05, 403.10, 401.40 and 400.05 eV ascribed to pyridinic N (Py−N), pyridinic N−O, quaternary N (Q−N) and pyrrolic N (Pr−N) respectively (Figure C) .…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescence quantum yields (QY) of the R-CDs were determined using a method described in the relevant literature. 32 Firstly, rhodamine B was selected as the reference material (QY = 56% in ethanol, 590–620 nm), and was then dissolved in ethanol, and an equal amount of the carbon dots in deionized water was also used. The UV absorption and fluorescence intensity of the carbon dots solution under irradiation with a specific excitation light were determined by controlling the temperature, concentration, and excitation wavelength, respectively.…”
Section: Methodsmentioning
confidence: 99%